Isolation and Characterization of Pseudomonas spp. Strains That Efficiently Decompose Sodium Dodecyl Sulfate - Furmanczyk, Ewa M.; Kaminski, Michal A.; Spolnik, Grzegorz; Sojka, Maciej; Danikiewicz, Witold; Dziembowski, Andrzej; Lipinski, Leszek; Sobczak, Adam (Frontiers in Microbiology, 2017)
Due to their particular properties, detergents are widely used in household cleaning products, cosmetics, pharmaceuticals, and in agriculture as adjuvants tailoring the features of pesticides or other crop protection agents. The continuously growing use of these various products means that water soluble detergents have become one of the most problematic groups of pollutants for the aquatic and terrestrial environments. Thus it is important to identify bacteria having the ability to survive in the presence of large quantities of detergent and efficiently decompose it to non-surface active compounds. In this study, we used peaty soil sampled from a surface flow constructed wetland in a wastewater treatment plant to isolate bacteria that degrade sodium dodecyl sulfate (SDS). We identified and initially characterized 36 Pseudomonas spp. strains that varied significantly in their ability to use SDS as their sole carbon source. Five isolates having the closest taxonomic relationship to the Pseudomonas jessenii subgroup appeared to be the most efficient SDS degraders, decomposing from 80 to 100% of the SDS present in an initial concentration 1 g/L in less than 24 h. These isolates exhibited significant differences in degree of SDS degradation, their resistance to high detergent concentration (ranging from 2.5 g/L up to 10 g/L or higher), and in chemotaxis toward SDS on a plate test. Mass spectrometry revealed several SDS degradation products, 1-dodecanol being dominant; however, traces of dodecanal, 2-dodecanol, and 3-dodecanol were also observed, but no dodecanoic acid. Native polyacrylamide gel electrophoresis zymography revealed that all of the selected isolates possessed alkylsulfatase-like activity. Three isolates, AP3_10, AP3_20, and AP3_22, showed a single band on native PAGE zymography, that could be the result of alkylsulfatase activity, whereas for isolates AP3_16 and AP3_19 two bands were observed. Moreover, the AP3_22 strain exhibited a band in presence of both glucose and SDS, whereas in other isolates, the band was visible solely in presence of detergent in the culture medium. This suggests that these microorganisms isolated from peaty soil exhibit exceptional capabilities to survive in, and break down SDS, and they should be considered as a valuable source of biotechnological tools for future bioremediation and industrial applications.